Taxonomy of Petrosiidae Van Soest, 1980 (Haplosclerida, Porifera) from Brazil - Rocha, Lívia; Moraes, Fernando; Salani, Sula; Hajdu, Eduardo (Zootaxa, 2021)
Petrosiidae (Haplosclerida, Demospongiae) is characterized by the hard and friable consistency, and an isotropic reticulated skeleton of oxeas/ strongyles. The Brazilian coast and oceanic islands harbor three out of four known genera of Petrosiidae: Neopetrosia de Laubenfels, 1949; Petrosia (Petrosia) Vosmaer, 1885 and Xestospongia de Laubenfels, 1932. A taxonomic survey of samples from several expeditions housed at the Porifera Collection of Museu Nacional, Universidade Federal do Rio de Janeiro, with additional comparative materials obtained from the Museu de Ciências Naturais, Fundação Zoobotânica do Rio Grande do Sul, and Universidade Federal de Pernambuco enabled the description of two new species: P. (P.) revizee sp. nov. and X. dorigo sp. nov. We also recorded a range extention for Neopetrosia proxima and Xestospongia muta, and Xestospongia grayi was synonymized with X. muta. Other species reported from the country are diagnosed, and an identification key for Petrosiidae from Brazil is provided.